Controlled-Channel Attacks: Deterministic Side Channels for Untrusted Operating Systems - Xu, Yuanzhong; Cui, Weidong; Peinado, Marcus (Proceedings of the 36th IEEE Symposium on Security and Privacy (Oakland), 2015)
The presence of large numbers of security vulnerabilities in popular feature-rich commodity operating systems has inspired a long line of work on excluding these operating systems from the trusted computing base of applications, while retaining many of their benefits. Legacy applications continue to run on the untrusted operating system, while a small hypervisor or trusted hardware prevents the operating system from accessing the applications’ memory. In this paper, we introduce controlled-channel attacks, a new type of side-channel attack that allows an untrusted operating system to extract large amounts of sensitive information from protected applications on systems like Overshadow, InkTag or Haven. We implement the attacks on Haven and InkTag and demonstrate their power by extracting complete text documents and outlines of JPEG images from widely deployed application libraries. Given these attacks, it is unclear if Overshadow’s vision of protecting unmodified legacy applications from legacy operating systems running on off-the-shelf hardware is still tenable.